2007
DOI: 10.1021/jp0755443
|View full text |Cite
|
Sign up to set email alerts
|

Post-Overoxidation Self-Recovery of Polypyrrole Doped with a Metallacarborane Anion

Abstract: By using the metallacarborane [Co(C2B9H11)2]-, [1]-, as a doping anion, PPy materials can be made 300−500 mV more resistant to overoxidation. These materials are written as PPy/[A] to indicate a noncovalency between the anion and the PPy and have a clear overoxidation resistance limit, ORL, so that once this is surpassed the material becomes permanently nonelectroactive or dead. On the contrary if [Co(C2B9H11)2]- is chemically bonded to pyrrole through a spacer and then is copolymerized with pyrrole the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The IR spectra of the polymers PEDOT:M[COSANE] do not show strong and sharp B−H bands, but a small and broad band. Previous studies have demonstrated that the metallacarborane with conducting polymers does not show strong and sharp B−H bands, but after the overoxidation of the polymer, a strong and sharp B−H band appears . Therefore, the small B−H band is characteristic of the metallacarborane as a doping agent of conducting polymers.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The IR spectra of the polymers PEDOT:M[COSANE] do not show strong and sharp B−H bands, but a small and broad band. Previous studies have demonstrated that the metallacarborane with conducting polymers does not show strong and sharp B−H bands, but after the overoxidation of the polymer, a strong and sharp B−H band appears . Therefore, the small B−H band is characteristic of the metallacarborane as a doping agent of conducting polymers.…”
Section: Resultssupporting
confidence: 83%
“…Metallacarboranes, of which cobaltabisdicarbollide, [Co(C 2 B 9 H 11 ) 2 ] − , denoted as [COSANE] − , is the most researched, are redox‐reversible highly stable species with large possibilities for functionalization. They have been utilized both as components of pendant arms and as doping agents with PPy and in a prospective PEDOT polymer . Cobaltabisdicarbollide has been proven to form hydrogen and dihydrogen bonds, interacting with weakly acidic X−H units or lone‐pair elements, and can self‐assemble in water to generate micelles and vesicles .…”
Section: Introductionmentioning
confidence: 99%
“…(1,2), meta-(1,7), and para- (1,12)) and metallacarboranes [3,3 0 -M(1,2-C 2 B 9 H 11 ) 2 ] À , M = Co(III) in (1) and M = Fe(III) in (2). Therefore, the nature of the counter-ion used in electropolymerization and the applied experimental conditions play a very important role in the resulting properties of the COP films.…”
Section: Conducting Organic Polymers Incorporating Icosahedral Bormentioning
confidence: 99%
“…Moreover, its power conversion efficiency exceeds that of the ferrocene-ferrocenium (Fc/Fc + ) couple by a factor of 90, and avoids the problem of electron interception by ferrocenium ion, thereby increasing the survival time of the electron in the photoelectrode. 81,82 In a direct application of this work to the fabrication of electronic devices, Teixidor and coworkers have constructed a 3D array of highly conducting polypyrrole microrings doped with Co(1,2-C 2 B 9 H 11 ) 2 − anions via surface patterning and electropolymerization. 78 A later modification, employing silica aerogels coated by atomic-layer-deposited TiO 2 in place of nanoparticles as a DSC platform, has led to greatly increased performance with photocurrent densities more than twice those of nanoparticle-based photoanodes.…”
Section: Carboranes In Electronic Devicesmentioning
confidence: 99%